2022
DOI: 10.3390/separations9060155
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Copper (II) Ions Removal by Reverse Osmosis under Various Operating Conditions

Abstract: The study aims to treat artificial wastewater contaminated with copper (II) ions by reverse osmosis using (SEPA CF042 Membrane Test Skid-TFC BW30XFR). Several concentrations of feedstock were prepared. Different operating pressure, temperature, and flow rate were applied. The effect of these operating conditions on both the amount of Cu (II) removal and the permeate flux was monitored. The results of the study revealed that both the permeate flux and Cu (II) removal amount were directly proportional to the ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…It was observed that when the pressure increased by 30 bar from 10 to 40 bar with a constant T of 25 °C, feed flow rate of 3.2 L/min, and initial concentration of 100 ppm, the permeate flux increased by 188% from 43.03 to 123.91 (kg/m 2 h) and increased by 94% when the pressure increased slightly by 10 bar from 10, by 29.6% when the applied pressure increased from 20 to 30 bar, and by 14.84% when the pressure increased from 30 to 40 bar for all tested concentrations due to the pressure acting as a driving force. Hence, the amount of solute crossing the membrane increased as described in [27,35,37,39,40], which state that the filtrate flow rate increases as the pressure increases. The impacts of the inlet temperature on the rejection % of nickel ions at various concentrations of the feed with a constant feed flow rate and pressure are presented in Figure 2b.…”
Section: Operating Pressure Effectmentioning
confidence: 92%
See 1 more Smart Citation
“…It was observed that when the pressure increased by 30 bar from 10 to 40 bar with a constant T of 25 °C, feed flow rate of 3.2 L/min, and initial concentration of 100 ppm, the permeate flux increased by 188% from 43.03 to 123.91 (kg/m 2 h) and increased by 94% when the pressure increased slightly by 10 bar from 10, by 29.6% when the applied pressure increased from 20 to 30 bar, and by 14.84% when the pressure increased from 30 to 40 bar for all tested concentrations due to the pressure acting as a driving force. Hence, the amount of solute crossing the membrane increased as described in [27,35,37,39,40], which state that the filtrate flow rate increases as the pressure increases. The impacts of the inlet temperature on the rejection % of nickel ions at various concentrations of the feed with a constant feed flow rate and pressure are presented in Figure 2b.…”
Section: Operating Pressure Effectmentioning
confidence: 92%
“…The feed water temperature has an impact on the performance of ROMs [33]. The flow of permeate increases with increasing temperature, as it decreases the solution's viscosity and increases the membrane surface diffusivity [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the recent literature on Cu removal by membrane filtration techniques is based on model solutions. As presented by researchers, it is possible to obtain a high Cu retention of Cu using polyethylenimine (PEI) cross-linked P84 NF membranes (>90%) [ 60 ], NF and FO process with piperazine/polyethyleneimine (PIP/PEI) membranes (95 and 99%, respectively) [ 61 ], NF like-forward osmosis (99.4%) [ 62 ], FO (95%) [ 63 ], RO (>90%) [ 64 ], NF (>90%) [ 65 ]. Moreover, with the support of Keggin polyoxometalates, the UF process allows one to obtain maximum metal retention at the level of 99% for Cd and Cu [ 66 ].…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%
“…Several chemical and physical technologies have been developed and used to remove Ni(II) ions from water and wastewater, including complexation or membrane filtration [5]; nanofiltration [6]; ultrafiltration [7]; photocatalytic removal [8,9,10]; electro-permutation [11]; electro-deionization [12,13]; electro-chemical reduction/oxidation [14]; electro-coagulation [15,16]; hybrid electro-coagulation or microfiltration [17]; electro-flotation [18]; co-precipitation [19]; reverse osmosis [20,21,22] complexation or ultrafiltration [23]; flotation [24,25]; ion exchange [26][27][28][29][30][31]; precipitation [24]; and coagulation or flocculation [32]. Traditional approaches, on the other hand, have drawbacks, including lower removal efficiency, sensitive operating conditions, high operational costs, and the formation of secondary sludge, which requires extra treatment.…”
Section: Introductionmentioning
confidence: 99%